The manufacturing in composite materials in Malaysian's industry / Nur Afni Abdullah and Rafidah Kamaruddin - Abdullah, Nur Afni; Kamaruddin, Rafidah (Faculty of Mechanical Engineering, 2003)
This report is purposely done to fulfil the requirement for the final year student in Diploma Mechanical Engineering to prepare a kind of thesis to submit as a final year project. The report is basically all about the manufacturing of composite materials in Malaysian’s industry. We are supposed to study about composite materials and their manufacturing process and applications through visiting the entire composite department to collect data of present production. Generally, we have consists the report with the theory of composite materials, the main case study of factory visited and process study, future recommendation and also some related figure related to the project.